Comprehensive in silico analysis to decipher the role of long non-coding RNAs in bread wheat during fusarium head blight and leaf rust interactions - Jyothsna S; Alagu Manickavelu (Academia Molecular Biology and Genomics)
The advancements in high-throughput sequencing technology have disclosed the substantial role of plant non-coding RNAs (ncRNAs), a relatively lessexplored but potent regulatory component, in fine-tuning plant responsestoabiotic and biotic stresses. Among these regulatory ncRNAs, long non-coding RNAs (lncRNAs) and microRNAs (miRNAs) are well-recognized robust regulatory elements that can modulate plant gene regulation at transcriptional, post-transcriptional, and epigenetic levels. Emerging empirical evidence supports the intricate orchestration of miRNA-lncRNA networks in regulating distinct aspects of plant–pathogen interactions. Leaf rust (LR) and fusarium head blight (FHB) are two seriousfungal diseases caused by Puccinia triticinaand Fusarium graminearum, which persistently affect wheat growth worldwide. The current study employs an in silico approach to predict differentially expressed lncRNAs (DElncRNAs) from two distinct wheat transcriptome studies under P. triticinaand F. graminearum infection. A total of 595 wheat DElncRNAs were predicted by implementing a stringent lncRNA selection criterion. The disclosure of lncRNAs acting as putative miRNA precursors, miRNA targets, and miRNA target mimics highlightsthe interdependence between miRNAs and lncRNAs during fungal invasions in wheat. In alignment with prior research, the sequence homology search of predicted DElncRNAs exhibited only marginal similarities with the other related crops. The functional annotation of lncRNA cis and trans targets unveiled the prevalence of defence and mycotoxin-related processes in FHB-infected samples, whereas LR infection primarily elicited oxidative stress and polyamine synthesis activities. Thisstudy unveils a potential functional divergence within lncRNAs and serves as a fine resource that can be harnessed to elucidate the interplay of miRNA-lncRNA-mRNA networks governing wheat–fungal interactions.